2001
DOI: 10.1258/0956462011923804
|View full text |Cite
|
Sign up to set email alerts
|

Mucocutaneous leishmaniasis in a patient with the human immunodeficiency virus

Abstract: We report a case of mucocutaneous leishmaniasis (MCL) in a patient with the human immunodeficiency virus (HIV), Centers for Disease Control (CDC) Stage A2, with no previous history of cutaneous or systemic leishmaniasis. The patient had not travelled outside the province of Málaga, on the Mediterranean coast of southern Spain, so that it concerns an indigenous case, extremely unusual in this area. The HIV infection may well have influenced the defence against leishmania, but the exact mechanism by which this o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…Furthermore, patients with HIV infection and mucosal leishmaniasis are predisposed to development of atypical lesions. Another constant preoccupation of clinicians is about the risk of mucosal disease become visceral 12–14 . The treatment depends of host, pathogen and direct effect of drug.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, patients with HIV infection and mucosal leishmaniasis are predisposed to development of atypical lesions. Another constant preoccupation of clinicians is about the risk of mucosal disease become visceral 12–14 . The treatment depends of host, pathogen and direct effect of drug.…”
Section: Discussionmentioning
confidence: 99%
“…Goh 8 et al in 2004 found it to be three times more common in patients with CD4 counts below 200. Sanchez et al 23 found that 80% of their patient had a CD4 cell count of < 100 cells / cumm. Higher mean CD4 count in current study may be due to the fact that 90% of Pruritic papular eruptions patients were on HAART and it could be due to IRIS (immune reconstitution inflammatory syndrome).…”
Section: Resultsmentioning
confidence: 94%